Performance evaluation of a solar powered electric vehicle - Hossain, Mohammad Tayef; Alave, Md Solaiman Bhuiyan; Saleheen, Kazi Mushfiqus; Karim, Syed Ashraful (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.